About big data and digital neo-positivism in history research - Tiago Luís Gil (Umanistica Digitale)
The paper discusses the progress of digital initiatives in historical research, highlighting in particular the increase in the number of large repositories and online archival collections. This scenario is seen as part of a growing attention to big data that has to be discussed in the disciplinary community. Some cases (such as Transkribus and Time Machine)  with a strong empiricist approach seem to prefigure a sort of irrelevance of the historical method through the emphasis given to disintermediation. The article hopes to provide ideas for the debate, indicating digital training as the essential condition to orient historians in the face of a sea of ​​uncertainties and algorithms.